Prevalence and factors associated with depression among higher secondary school adolescents of Pokhara Metropolitan, Nepal: a cross-sectional study. Issue 12 (31st December 2020) - Bhattarai, Deepa; Shrestha, Nisha; Paudel, Shishir
Abstract : Objective: This study examined the prevalence and factors associated with depression among adolescents attending higher secondary schools in the Pokhara Metropolitan City of Nepal. Design: A cross-sectional study design was adopted. Setting: Four randomly selected higher secondary schools of Pokhara Metropolitan, Nepal. Participants: 312 randomly sampled higher secondary school students. Methods: The Center for Epidemiologic Studies Depression Scale was used to assess the level of depression among students. The data collected through a self-administered questionnaire were analysed using descriptive statistical methods such as frequency and percentage. χ 2 test and unadjusted OR (UOR) were calculated to assess the statistical relationship between depression and various variables at 95% CI, with level of significance at p<0.05. Results: The study found a high prevalence of depression among high school students, with more than two-fifths (44.2%) of students having depression. Furthermore, almost a quarter (25.3%) of the students were noted to have mild depression and 18.9% of the students expressed major depression. Students who had low perceived social support (UOR: 3.604; 95% CI 2.088 to 6.220), did not share their problems with anyone (UOR: 1.931; 95% CI 1.228 to 3.038) and had low self-esteem (UOR: 5.282; 95% CI 2.994 to 9.319) were at higher odds of being depressed. Conclusion: A high prevalence of depression was observed among high school students. It was also observed that students' level of perceived social support, self-esteem and help-seeking behaviour are somehow related to their mental well-being. Hence, improving social support and self-esteem may alleviate depression and mental distress among these adolescents.